(untitled) (Bangladesh Journal of Nuclear Medicine, 2018)
Hydatid disease is caused by Echinococcus granulosus and is endemic in many parts of the worlds and produce cysts in almost every organs of the body, with the liver and lung being the most common sites. Here we presented a case of isolated retro-vesical hydatid cyst which is extremely rare with only a few cases reported in literature previously. Bangladesh J. Nuclear Med. 18(2): 186-188, July 2015